West African College of surgeons basic ophthalmology resource: development and initial evaluation (2024)
Purpose: To describe the process of development of the West African College of Surgeons (WACS) Basic Ophthalmology Educational Resource and to report the feedback from the first five cohorts to utilise the resource at the commencement of their training in ophthalmology. Methods: After initial meetings topics considered essential foundations for training in ophthalmology were identified. Faculty members subsequently searched the internet to identify suitable online open source learning materials relevant to each topic, which were then collated and cataloged. Where suitable quality learning materials could not be identified, materials were created or re-used from existing WACS courses. Following the creation of the resource, questions were developed for a summative assessment, taken by learners upon completion of the resource. Results: The resource went 'live' on 10th July 2019. As of March 2024, a total of 203 learners in 5 cohorts had completed the course. The feedback responses of 150 (74%) learners from the first 5 cohorts are described in this report. Regarding their overall assessment of the course, 64 (43%) learners rated the resource as very good', 63 (42%) as 'good', and 23 (15%) as 'satisfactory’. Most (>98% respondents reported that the course met their expectations and that the content was relevant to their learning needs. Conclusion: The WACS Basic Ophthalmology Resource appears to be a valuable opportunity for acquiring foundational knowledge.